2017
DOI: 10.1038/ncomms14935
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the complex free-energy landscape of the simplest glass by rheology

Abstract: For amorphous solids, it has been intensely debated whether the traditional view on solids, in terms of the ground state and harmonic low energy excitations on top of it, such as phonons, is still valid. Recent theoretical developments of amorphous solids revealed the possibility of unexpectedly complex free-energy landscapes where the simple harmonic picture breaks down. Here we demonstrate that standard rheological techniques can be used as powerful tools to examine nontrivial consequences of such complex fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
82
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 61 publications
10
82
3
Order By: Relevance
“…Remarkably, the phase diagrams shown in Fig. 1 are qualitatively similar to those obtained in numerical simulations of three-dimensional systems [38,39], for which we also note that for increasing preparation density ϕ g , the values of the yield strain γ Y and the yield stress increase as well. The main qualitative difference is the shape of the shear jamming and shear yielding curves in the vicinity of the critical point where they merge, which might be explained by RSB effects.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Remarkably, the phase diagrams shown in Fig. 1 are qualitatively similar to those obtained in numerical simulations of three-dimensional systems [38,39], for which we also note that for increasing preparation density ϕ g , the values of the yield strain γ Y and the yield stress increase as well. The main qualitative difference is the shape of the shear jamming and shear yielding curves in the vicinity of the critical point where they merge, which might be explained by RSB effects.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the theory has been extended to hard sphere with a short range attraction [33], to investigate a peculiar two-step yielding transition that characterizes colloidal systems [34]. These predictions, obtained in the mean-field d → ∞ limit, have been partially confirmed by extensive numerical simulations in d = 3 [35][36][37][38][39] and experiments on a granular material in d = 2 [40].…”
Section: Introductionmentioning
confidence: 84%
“…In particular, around jamming it is found that µ(∆ EA ) ∼ P κ while µ(∆ < ∆ EA ) ∼ P µ(∆ EA ), hence a dramatic softening should be observed if the system is allowed to leave the glass state in which it was prepared. This theoretical prediction for d → ∞ systems has been verified numerically 111,125…”
Section: B Linear Responsementioning
confidence: 61%
“…On the other hand, it is unlikely that a Gardner phase can exist in dimensions as low as d = 2, where jamming criticality remains similar to the one in d = ∞ [15,16,18,21], suggesting that the Gardner transition, in itself, is not needed for a theory to capture the jamming criticality. Resolving this paradox is important, as mean-field theory can be used to tackle a large number of physical questions from a fully microscopic perspective, such as thermodynamic properties [4,19,[22][23][24], the structure of phase space, the evolution of vibrational dynamics [25,26], or the rheology of hard sphere glasses [27][28][29]. In addition, it is also important to understand under which conditions a complex free energy landscape may become physically relevant, in order to make novel predictions for experimental work dealing with the glassy dynamics of granular, colloidal, and molecular systems.…”
Section: Introductionmentioning
confidence: 99%